Strengthening International Legal Cooperation to Combat the Illegal Wildlife Trade Between Southeast Asia and China - Jiao, Yunbo; Yeophantong, Pichamon; Lee, Tien Ming (Frontiers in Ecology and Evolution, 2021)
China is among the world’s leading consumer markets for wildlife extracted both legally and illegally from across the globe. Due to its mega-richness in biodiversity and strong economic ties with China, Southeast Asia (SEA) has long been implicated as a source and transit hub in the transnational legal and illegal wildlife trade with China. Although several cross-border and domestic wildlife enforcement mechanisms have been established to tackle this illegal trade in the region, international legal cooperation and policy coordination between China and its SEA neighbors remain limited in both scope and effectiveness. Difficulties in investigating and prosecuting offenders in overseas jurisdictions, as well as organized criminal groups that sustain the illicit supply chain, continue to undermine efforts by the region’s governments to combat wildlife trafficking. In addition to reviewing the key trends in both the legal and illegal wildlife trade between SEA and China, this paper examines existing legal and policy frameworks in China and SEA countries, and provides a synthesis of evidence on the latest developments in regional efforts curtail this multibillion-dollar trade. In particular, it discusses how proactive and effective China has been in cooperating with its SEA neighbors on this issue. The paper also draws on the United Nations Convention against Transnational Organized Crime (UNTOC) framework to suggest pathways to deepen legal cooperation between China and SEA countries in order to disrupt and dismantle transnational wildlife trafficking in the region.